Museum Anthropology and its Impact on the Marketing Mix of Museum Tourism Activity: An Exploratory Study in the Iraqi Museum: Museum Antropologi dan Dampaknya terhadap Campuran Pemasaran Aktivitas Pariwisata Museum: Studi Eksploratori di Museum Irak - Dr. Sheimaa Hameed Rasheed (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Museums play an important role in preserving cultural heritage and supporting cultural tourism development through effective management and interpretation of archaeological collections. Knowledge Gap: Despite Iraq’s rich archaeological heritage, the integration of museum anthropology within the marketing mix of museum tourism remains limited, resulting in a gap between heritage potential and actual tourism marketing practices. Aims: This study aims to analyze the role of museum anthropology dimensions in shaping the marketing mix strategies of museum tourism in Iraq and to identify their contribution to improving tourism performance in museums. Results: Using a descriptive analytical approach and data collected from 92 respondents working in the Iraqi Museum and the State Board of Antiquities and Heritage, the museum anthropology has a statistically significant relationship with the 4Cs marketing mix. The spatial dimension demonstrates the strongest contribution to visitor value, pricing, place, and communication elements within the museum tourism marketing framework. Novelty: The study provides an integrated analytical model linking museum anthropology dimensions with the 4Cs marketing mix within the context of Iraqi museum tourism. Implications: The findings highlight the need for modern marketing strategies, improved interpretation of cultural heritage, stronger institutional collaboration to support sustainable museum tourism development. Keywords: Museum Anthropology, Museum Tourism, Marketing Mix, Cultural Heritage, Tourism Marketing Key Findings Highlights Spatial aspects of museum anthropology show the strongest statistical relationship with the tourism marketing framework. Museum operations still rely heavily on traditional exhibition practices with limited interpretive communication. Archaeological heritage resources remain underutilized within structured tourism management strategies.